التشحم الكبدي الحاد خلال الحمل - حايك, ميس (Latakia University Journal -Medical Sciences Series, 2019)
ACUTE FATTY LIVER OF PREGNANCY (AFLP) , a life threatening obstetric emergency, was first described by Sheehan in 1940.The most common presentation is malaise, nausea, vomiting and epigastric pain followed by jaundice. Laboratory tests usually demonstrate high bilirubin levels, deranged liver and renal functions, coagulopathy and hypoglycemia. one should keep in mind other pregnancy related liver diseases that mimic AFLP such as HELLP syndrome: hemolysis (H), elevated liver enzymes (EL) and low platelet count (LP), and intrahepatic cholestasis of pregnancy. Liver biopsy is the gold standard for diagnosing AFLP, but due to the presence of coagulation abnormalities diagnosis is usually made by clinical and laboratory findings. تشحم الكبد الحاد بالحمل : هو حالة توليدية إسعافيه مهددة للحياة ,وصفت لأول مرة من قبل شيهان عام 1940. العرض الرئيسي الاشيع هو الدعث , الغثيان , الاقياء و الألم الشرسوفي الذي يسبق اليرقان تبدي التحاليل المخبرية عادة ارتفاع البيلروبين ,اختلال بأنزيمات الكبد و الكلية , اعتلال تخثر و نقص سكر . يجب أن نتذكر دائما أمراض الكبد الأخرى المتعلقة بالحمل و التي تتشابه مع AFLP( تشحم الكبد الحاد )مثل : *- متلازمة هيلب (انحلال دم, ارتفاع خمائر الكبد ,و نقص الصفيحات ) *- الركودة الحملية الصفراوية . إن التشخيص الذهبي لتشحم الكبد الحاد هو خزعة الكبد , و لكن تبعاً لاعتلال التخثر فالتشخيص يكون سريرياٌ ومخبرياً.